Myrtucommulone from Myrtus communis: Metabolism, Permeability, and Systemic Exposure in Rats - Gerbeth, Kathleen; Hüsch, Jan; Meins, Jürgen; Rossi, Antonietta; Sautebin, Lidia; Wiechmann, Katja; Werz, Oliver; Skarke, Carsten; Barrett, Jeffrey S.; Schubert-Zsilavecz, Manfred; Abdel-Tawab, Mona (Planta Medica, 2012)
Nonsteroidal anti-inflammatory drug intake is associated with a high prevalence of gastrointestinal side effects, and severe cardiovascular adverse reactions challenged the initial enthusiasm in cyclooxygenase-2 inhibitors. Recently, it was shown that myrtucommulone, the active ingredient of the Mediterranean shrub Myrtus communis, dually and potently inhibits microsomal prostaglandin E2 synthase-1 and 5-lipoxygenase, suggesting a substantial anti-inflammatory potential. However, one of the most important prerequisites for the anti-inflammatory effects in vivo is sufficient bioavailability of myrtucommulone. Therefore, the present study was aimed to determine the permeability and metabolic stability in vitro as well as the systemic exposure of myrtucommulone in rats. Permeation studies in the Caco-2 model revealed apparent permeability coefficient values of 35.9 · 10−6 cm/s at 37 °C in the apical to basolateral direction, indicating a high absorption of myrtucommulone. In a pilot rat study, average plasma levels of 258.67 ng/mL were reached 1 h after oral administration of 4 mg/kg myrtucommulone. We found that myrtucommulone undergoes extensive phase I metabolism in human and rat liver microsomes, yielding hydroxylated and bihydroxylated as well as demethylated metabolites. Physiologically-based pharmacokinetic modeling of myrtucommulone in the rat revealed rapid and extensive distribution of myrtucommulone in target tissues including plasma, skin, muscle, and brain. As the development of selective microsomal prostaglandin E2 synthase-1 inhibitors represents an interesting alternative strategy to traditional nonsteroidal anti-inflammatory drugs and cyclooxygenase-2 inhibitors for the treatment of chronic inflammation, the present study encourages further detailed pharmacokinetic investigations on myrtucommulone.
Keywords: myrtucommulone; Myrtus communis; Myrtaceae; myrtle; rat plasma; Caco-2; metabolism; physiologically-based pharmacokinetic modeling